The First 2,000 Days and Child Skills - Doyle, Orla (Journal of Political Economy, 2020)
Using a randomized experiment, this study investigates the impact of sustained investment in parenting, from pregnancy until age 5, in the context of extensive welfare provision. Providing the Preparing for Life program, incorporating home visiting, group parenting, and baby massage, to disadvantaged Irish families raised children’s cognitive and socioemotional/behavioral scores by two-thirds and one-quarter of a standard deviation, respectively. There were few differential effects by gender and stronger gains for firstborns and lower-resource households. The program also narrowed the socioeconomic gap in children’s skills. Analyses account for small sample size, differential attrition, multiple testing, contamination, and performance bias.